The effectiveness of book voucher / Danny Edwin and Noor Azyra Sabri - Edwin, Danny; Sabri, Noor Azyra (2013)
School voucher systems come in a variety of flavors, one of them is 1 Malaysia Book Voucher or Baucar Buku 1 Malaysia (BB1M). The 1 Malaysia Book Voucher or Baucar Buku 1 Malaysia (BB1M) is an initiative by the Ministry of Higher Education (MOHE) in 2012 to help ease the financial burden of tertiary students all over Malaysia as well as help these students get better access to books and stationery that would help them with their studies.